Structure of the Holliday junction: applications beyond recombination. (15th October 2017) - Ho, P. Shing
Abstract : The Holliday junction (HJ) is an essential element in recombination and related mechanisms. The structure of this four-stranded DNA assembly, which is now well-defined alone and in complex with proteins, has led to its applications in areas well outside of molecular recombination, including nanotechnology and biophysics. This minireview explores some interesting recent research on the HJ, as it has been adapted to design regular two- or three-dimensional lattices for crystal engineering, and more complex systems through DNA origami. In addition, the sequence dependence of the structure is discussed in terms how it can be applied to characterize the geometries and energies of various noncovalent interactions, including halogen bonds in oxidatively damaged (halogenated) bases and hydrogen bonds associated with the epigenetic 5-hydroxylmethylcytosine base.